DINAMIKA ISLAM MODERN DI INDONESIA: Kajian Paradigma, Faktor, dan Implikasinya Terhadap Wacana Sosio-Intelektual - Walkaromah, Naylul Izzah; Mubaraq, Zulfi; Mustofa, M. Lutfi; Toriquddin, Moh. (State Islamic University of Datokarama Palu, 2024)
The study of modern Islamic thought in Indonesia is very important to be studied more deeply. This is because the study never ceases to be debated. The purpose of this paper is to understand 3 things: First, the paradigm of modern Islamic thought. Second, the internal and external factors that influence modern Islam. Third, the positive and negative implications of modern Islam on Islamic socio-intellectual discourse in Indonesia. The method used is library research with a qualitative approach, the data is analyzed using content analysis techniques. The results found are three things: First, there are 4 forms of modern Islamic thought paradigm in Indonesia: reform, evolutionary, progressive, adaptive. Second, internally there are 3 factors that influence it: (1) the demand for renewal of Islamic teachings that are too taqlid and rigid (2) awareness of purifying Islamic practices (3) the Islamic press movement spread widely. As for externally, there are 3 factors that influence it: (1) the influence of modernity in the Western world (2) the dominance of Middle Eastern clerical thought (3) the reality of competition from other cultures and religions. Third, the positive implications of modern Islam for Islam in Indonesia are three things: (1) progressiveness in various fields (2) Islamic teachings are more rational (3) Islamic thought exists and is relevant to the contemporary context. Meanwhile, the negative implications of modern Islam on Islam in Indonesia are 3 things: (1) conflict between community groups (2) rejection from conservative groups (3) marginalization of figures and extremism tendencies. The conclusion of this paper shows that modern Islamic thought in Indonesia contains complex dynamics in shaping the social life of Muslims in Indonesia.